Radiation Oncology Follow-Up of Prostate Cancer Survivors Following Completion of Radiotherapy: A Population-Based Study. - Cerasuolo, Joshua O.; Sussman, Jonathan; Dayes, Ian S.; Sutradhar, Rinku; Zargoush, Manaf; Seow, Hsien (Current Oncology, 2026)
Simple Summary: Prostate cancer survivors often need long-term follow-up to manage side effects of treatment and monitor relapse or progression. It is unknown which patients seek routine follow-up visits, and how often, at specialized cancer hospitals. In this study, we looked at which patient characteristics were related to how frequently survivors saw their radiation oncologist, starting three years after completing radiation treatment. We found that patients at higher risk had more frequent follow-up visits with radiation oncology, while lower-risk patients were seen less. Overall, the number of survivors returning for radiation oncology follow-up dropped by more than 46% over five years, which suggests that care is being tapered appropriately over time. Still, more than 23% of survivors were seeing their radiation oncologist in the fifth year after treatment, and over half of these patients were considered lower risk. This shows that even though follow-up generally aligned with patients' needs, many lower-risk survivors continued longer-term follow-up with radiation oncology. Transitioning the ongoing care of lower-risk patients to their primary care providers enables long-term follow-up closer to home, while ensuring a sustainable cancer care system. Prostate cancer survivors require coordinated long-term care after treatment. We examined patterns of follow-up care and identified characteristics associated with the frequency of radiation oncology (RO) visits during survivorship. We conducted a population-based cohort study of men diagnosed with prostate cancer between April 2010 and March 2019 in Ontario, Canada, who underwent first-line radiotherapy. Survivorship began three years following radiation. Using a recurrent event framework, we identified demographic and clinical characteristics associated with the rate of RO follow-up. Survivors seeking RO follow-up declined by 46.2% over five years of survivorship. Higher-risk characteristics, such as higher ISUP grade, higher stage, detectable prostate-specific antigen (PSA) score, and receipt of brachytherapy and/or hormones, were associated with more frequent RO visits. For instance, relative to International Society of Urological Pathology (ISUP) Grade 1, those with Grades 3 through 5 experienced follow-up rates that were 20%, 25%, and 34% higher, respectively. Despite concordance between patient risk and rate of RO follow-up, 23.6% of survivors continued to visit their RO providers into their fifth year of survivorship, more than half of whom were ISUP grades 1–2. Primary care follow-up remained stable. While frequency of RO follow-up appropriately reflected patient risk profile, many low-risk survivors still sought long-term RO-led care. This suggests an opportunity to encourage lower-risk prostate cancer survivors to seek follow-up care with their general practitioner.